SARS-CoV-2 D614G variant exhibits efficient replication ex vivo and transmission in vivo - Hou, Yixuan J.; Chiba, Shiho; Halfmann, Peter; Ehre, Camille; Kuroda, Makoto; Dinnon, Kenneth H.; Leist, Sarah R.; Schäfer, Alexandra; Nakajima, Noriko; Takahashi, Kenta; Lee, Rhianna E.; Mascenik, Teresa M.; et al. (Science (American Association for the Advancement of Science), 2020)
Pandemic spread of a virus in naïe populations can select for mutations that alter pathogenesis, virulence, and/or transmissibility. The ancestral form of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that emerged from China has now been largely replaced by strains containing the mutation D614G (Asp 614 -to-Gly) in the viral spike protein. Hou et al. compared the characteristics of the new variant against the ancestral form in a series of experiments in human cells and animal models. The variant is better at infecting upper-airway epithelial cells and replicates in greater numbers than the ancestral virus. Evidence indicates modest, if any, significant changes to virulence in animal models. Therefore, the virus appears to have evolved for greater transmissibility in humans rather than for greater pathogenicity. The mutation renders the new virus variant more susceptible to neutralizing antisera without altering the efficacy of vaccine candidates currently under development. Science , this issue p. 1464 The current dominant structural variant of SARS-CoV-2 appears to have evolved from the ancestral form and enhances transmissibility. The spike aspartic acid–614 to glycine (D614G) substitution is prevalent in global severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strains, but its effects on viral pathogenesis and transmissibility remain unclear. We engineered a SARS-CoV-2 variant containing this substitution. The variant exhibits more efficient infection, replication, and competitive fitness in primary human airway epithelial cells but maintains similar morphology and in vitro neutralization properties, compared with the ancestral wild-type virus. Infection of human angiotensin-converting enzyme 2 (ACE2) transgenic mice and Syrian hamsters with both viruses resulted in similar viral titers in respiratory tissues and pulmonary disease. However, the D614G variant transmits significantly faster and displayed increased competitive fitness than the wild-type virus in hamsters. These data show that the D614G substitution enhances SARS-CoV-2 infectivity, competitive fitness, and transmission in primary human cells and animal models.